General Family of Third Order Methods for Multiple Roots of Nonlinear Equations and Basin Attractors for Various Methods. (31st March 2014) - Sharma, Rajni; Bahl, Ashu
Abstract : A general scheme of third order convergence is described for finding multiple roots of nonlinear equations. The proposed scheme requires one evaluation off, f ′, andf ′′ each per iteration and contains several known one-point third order methods for finding multiple roots, as particular cases. Numerical examples are included to confirm the theoretical results and demonstrate convergence behavior of the proposed methods. In the end, we provide the basins of attraction for some methods to observe their dynamics in the complex plane.